Russia and the WTO : The "Gravity" of Outsider Status - Lissovolik, Yaroslav (IMF Working Papers; Working Paper, 2004)
With China's accession to the WTO in 2001, Russia is by far that organization's most prominent nonmember. This paper applies the gravity model to gauge whether this "outsider" status has been affecting Russia's export structure. On the basis of cross-section and panel regressions for 1995-2002, we find that Russian exports to WTO members have fallen short of the model's predictions. The paper discusses possible explanations of this result, including Russia's exclusion from various WTO procedures, although own-export restrictions could have a similar effect. The model points to Russia's further trade reorientation toward WTO members after a putative accession. Our results also prompt some ideas that may resolve the recent empirical controversy over the WTO's overall role in promoting trade.